2017
DOI: 10.18632/oncotarget.19960
|View full text |Cite|
|
Sign up to set email alerts
|

A RasGAP, DAB2IP, regulates lipid droplet homeostasis by serving as GAP toward RAB40C

Abstract: Lipid droplet (LD) homeostasis involves activities of various RAB small GTPases. Recently, we found RAB40C was one of the RAB proteins regulating LD homeostasis. RAB40C contains a unique SOCS domain that is required for clustering of LDs. However, its precise functional role in LD homeostasis and mechanism of regulation remain largely unknown. In this study, we observed over-accumulation of LDs in cells with RAB40C deleted by Crispr-Cas9 editing. RAB40C appeared to reduce LD accumulation after long term incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
8
2
1
Order By: Relevance
“…Rab40B has been recently reported to regulate EPLIN and actin cytoskeleton dynamics (Linklater et al, 2021). Rab40C interacts with LDs and modulates LD biogenesis and mobilization (Luo et al, 2017;Tan et al, 2013). We demonstrated that the Drosophila Rab40 promote lipophagy process by regulating Golgi organization and the distribution of lysosomal protein Lamp1.…”
Section: Introductionmentioning
confidence: 66%
“…Rab40B has been recently reported to regulate EPLIN and actin cytoskeleton dynamics (Linklater et al, 2021). Rab40C interacts with LDs and modulates LD biogenesis and mobilization (Luo et al, 2017;Tan et al, 2013). We demonstrated that the Drosophila Rab40 promote lipophagy process by regulating Golgi organization and the distribution of lysosomal protein Lamp1.…”
Section: Introductionmentioning
confidence: 66%
“…There is no evidence to date for a role of Rab40a and Rab40b on LDs. However, Rab40c has been reported on LDs, and deletion of Rab40c or overexpression of its GTPase activating protein (GAP) disabled homologue 2 interacting protein (DAB2IP) caused accumulation of LDs [58,59]. While the role of Rab40c in LDs is unknown, there are reports linking it to degradation of other proteins.…”
Section: Rab40cmentioning
confidence: 99%
“…3 (Gasper et al, 2010;Kontani et al, 2002;Ogita et al, 2015). 4 (Luo et al, 2017). 5 (Nobes et al, 1998).…”
Section: Western Blotting and Antibodiesunclassified
“…13 (Jacob et al, 2016;Li et al, 2015). 14 (Lee et al, 2007;Luo et al, 2017;Rodriguez-Gabin et al, 2004). 15 (Mouly et al, 2019;Okada et al, 2015;Riou et al, 2010).…”
Section: Western Blotting and Antibodiesmentioning
confidence: 99%